2018
DOI: 10.1177/2280800017753948
|View full text |Cite
|
Sign up to set email alerts
|

The influence of Ca substitution on LaFeO3 nanoparticles in terms of structural and magnetic properties

Abstract: Background: The nanocrystalline structure of La 1-x Ca x FeO 3 was prepared by a sol-gel method involving an autocombustion process. The incorporation of rare-earths in LaFeO 3 induces strain in magnetic properties, especially in terms of the following parameters: replacement amount, oxygen partial pressure, and calcination temperature. Methods: To determine the effects of the amount of Ca 2+ ion doping agent and the calcination temperature on the microstructure, particle morphology, and magnetic properties of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 34 publications
(59 reference statements)
1
11
0
Order By: Relevance
“…In this regard, it must be mentioned that different parameters such as preparation method, 17 thermal treatment, 17,20,21 crystallite size, 18 morphology, 21 nature of doped cation, [12][13][14][15][16]22 and dopant concentration, 16,22 etc. have a significant impact on the magnetic [16][17][18][20][21][22][23][24][25] and dielectric 21 properties of LaFeO 3 -based materials. In this sense, preparation methods and their parameters have a notable effect on the properties of LaFeO 3 nanoparticles.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In this regard, it must be mentioned that different parameters such as preparation method, 17 thermal treatment, 17,20,21 crystallite size, 18 morphology, 21 nature of doped cation, [12][13][14][15][16]22 and dopant concentration, 16,22 etc. have a significant impact on the magnetic [16][17][18][20][21][22][23][24][25] and dielectric 21 properties of LaFeO 3 -based materials. In this sense, preparation methods and their parameters have a notable effect on the properties of LaFeO 3 nanoparticles.…”
Section: Introductionmentioning
confidence: 99%
“…22 Lin and coauthors have studied the effect of Ca substitution on the magnetic properties of LaFeO 3 . 23 Wei et al have demonstrated the higher magnetic and photocatalytic properties of Mn-doped LaFeO 3 compared to LaFeO 3 . 24 Ce doping has been observed to enhance the magnetic properties of LaFeO 3 in comparison with undoped LaFeO 3 and solution combustion synthesis has been found to be a more effective preparation process as compared to the coprecipitation method, and it has a better impact on the physicochemical properties of Ce-doped LaFeO 3 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…LaFeO 3 is a semiconductor/insulator perovskite oxide and its derived compounds by replacement of some of La atoms by other Re or alkaline earth (Ae) elements give rise to significant physical and chemical properties with promising applications in advanced technologies as in electronics, magnetics, fuel cells, gas sensors, and catalysts [1]. By partially exchanging La in the parent compound with other Re or Ae (La 1-x A x FeO 3 , A: Re or Ae) lead to structurally distorted compounds, and induce different lattice parameters and unit cell volumes [2][3][4]. In addition, Ae doping has an influence on particle size (PS) and grain size (R G ).…”
Section: Introductionmentioning
confidence: 99%
“…Oxygen deficiency leads to decrease the number of Fe 4+ , and excess oxygen leads to increase the number of Fe 4+ . Furthermore, doping at La site and O vacancy, have a direct impact on the local environment of Fe ions [4] and thereby resistivity. In addition, the difference of ionic radii of La-site ions in the compound and the difference of ionic radii of Fe +3 and Fe +4 have an influence on lattice and electrical properties.…”
Section: Introductionmentioning
confidence: 99%